Responses of Membranes and the Photosynthetic Apparatus to Salt Stress in Cyanobacteria - Yang, Wenjing; Wang, Fang; Liu, Lu-Ning; Sui, Na (Frontiers in Plant Science, 2020)
Cyanobacteria are autotrophs whose photosynthetic process is similar to that of higher plants, although the photosynthetic apparatus is slightly different. They have been widely used for decades as model systems for studying the principles of photosynthesis, especially the effects of environmental stress on photosynthetic activities. Salt stress, which is the most common abiotic stress in nature, combines ionic and osmotic stresses. High cellular ion concentrations and osmotic stress can alter normal metabolic processes and photosynthesis. Additionally, salt stress increases the intracellular reactive oxygen species (ROS) contents. Excessive amounts of ROS will damage the photosynthetic apparatus, inhibit the synthesis of photosystem-related proteins, including the D1 protein, and destroy the thylakoid membrane structure, leading to inhibited photosynthesis. In this review, we mainly introduce the effects of salt stress on the cyanobacterial membranes and photosynthetic apparatus. We also describe specific salt tolerance mechanisms. A thorough characterization of the responses of membranes and photosynthetic apparatus to salt stress may be relevant for increasing agricultural productivity.